Research Trends in the Indonesian Elementary School Literacy Movement: From Number of Publications, Research Approaches, to Findings - Yudianto, Asep; Mustadi, Ali; Mokhsein, Siti Eshah Binti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The implementation of literacy in Indonesian elementary schools (SD) in the era of information and technology plays a key role in equipping the younger generation with language and critical thinking skills to face future challenges. This article aims to analyze the implementation of literacy in Indonesian elementary schools from 2019 to 2023 through a literature review by understanding trends ranging from the number of publications, research approaches, subjects, sub-studies, instruments, data analysis, to findings related to literacy implementation. This research method uses a qualitative approach through a narrative literature review by grouping similar extracted data according to the results measured to answer the research objectives. The research results show that there were differences in the number of publications from year to year with a decrease in 2020 and an increase in 2021 and 2022, but decreased again in 2023. Quantitative research dominates and is followed by qualitative research. Most research subjects were fourth grade students and teachers. The most researched sub-study of literacy is scientific literacy. The data collection instruments commonly used are tests with the most frequently used data analysis method being descriptive statistics. The findings illustrate the importance of literacy in elementary school students' learning, supported by GLS and the effectiveness of inquiry learning models, interactive media, STEM approaches, and digital literacy in increasing students' literacy skills and motivation. Collaboration in developing literacy in various aspects of elementary school learning is very necessary. The research results concluded that the number of publications fluctuated, with dominant research on fourth grade students and teachers, focused on scientific literacy, used tests as the main instrument, and emphasized the importance of developing teacher digital literacy and numeracy through collaboration.